The Implication Of The Land Registration Program On Agrarian Reform In Kalongliud Village, Nanggung Subdistrict, Bogor Regency - Kalbu, Ahmad Buhaeri; Purwaningsih, Prihatini; Aminda, Annisa (Universitas Ibn Khaldun Bogor, 2025)
This research examines the impact of the land registration program within the framework of agrarian reform in Kalongliud Village, Nanggung Subdistrict, Bogor Regency. Land registration, as a crucial component of agrarian reform, is evaluated in terms of its effects on legal certainty, economic welfare, and social justice related to land tenure and utilization. The land registration program provides legal guarantees through land certificates, which serve as valid proof of ownership, thereby reducing the potential for land disputes and enhancing the sense of security among community members. Additionally, land registration increases the economic value of land, facilitates access to business capital, and improves the economic well-being of the community—aligning with the objectives of agrarian reform. However, residents who have not participated in the land registration program express concerns due to the lack of legal certainty. Consequently, land registration plays a pivotal role in achieving the goals of agrarian reform in Kalongliud Village.